Alongshore Propagation of Subtidal Sea Level Fluctuations Around the Korean Peninsula Over Varying Stratification and Shelf Topography - Lee, KyungJae; Nam, SungHyun; Park, Jae-Hyoung (Frontiers in Marine Science, 2022)
Understanding subtidal (a period band of 3–20 days) coastal sea level fluctuations is of increasing importance for the sustainable use of coastal areas under challenging conditions resulting from regional and global sea-level rise. The wind-forced coastal trapped wave (CTW) theory often accounts for subtidal sea level fluctuations observed off global coasts with a considerable range of propagation speeds. Here, the propagation speeds of subtidal sea level fluctuations observed at seven coastal tide-gauge stations around the Korean Peninsula (KP) from 1997 to 2017 were compared with phase speeds modeled for 10 segments of realistic bottom topography around the KP and four seasons of density stratification using a wind-forced CTW model. Alongshore variations in the modeled phase speed (2.0–10.0 m s-1, increasing with the bottom depth, shelf width, and vertical density difference) were consistent with those of the observed propagation speed (4.7–18.9 m s-1), despite systematic underestimation by 50%, i.e., the mean speed of 6.0 vs 11.8 m s-1. This underestimation is discussed considering subtidal sea level fluctuations of non-CTW origin that were not incorporated into the CTW model, such as 1) barometric sea level response to atmospheric pressure disturbances, and 2) upwelling/downwelling response to local alongshore wind stress. This study suggests that subtidal coastal sea level fluctuates around the KP within and beyond CTW dynamics.